Retro atelier Bulacan recycled furniture manufacturing complex - Nimes, Abba May M. (College of Architecture, University of the Philippines Diliman, 2014)
The Philippines is commonly recognized through woven, inlaid, and assembled wooden furniture. Its furniture industry is among the internationally well-known manufacturer of furniture in Southeast Asia. In the past year, the annual event of Philippine furniture industry promoted the concept of “Greenovation”, which encourages furniture manufacturers to use recyclable materials in designing furniture. This study is a response to the advocacy of Philippine furniture industry which is to design a furniture manufacturing complex centered on recyclable production that showcases Bulacan’s craftsmanship in furniture industry. In designing the complex, the concepts of “Retro” which is about a vintage modernism and “Atelier” that talks about the intricate details of design are considered. They are translated into “tongue and groove” for interlocking connection of spaces and the intricacy of the design of the furniture was put into the fine details of the structural elements. The proposed spaces like the commercial area, production building, MRF and auditorium are interlocked together through the central atrium. These spaces are enclosed with intricate structural elements which created a vintage ambiance to the project. This proposed built environment for the Bulacan Furniture Manufacturing Complex, embodies the identity of furniture production in the city making it a catalyst for advancing the furniture manufacturing of the company.